2011
DOI: 10.1002/cncr.26449
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecule protein signature in ovarian cancer effusions is prognostic of patient outcome

Abstract: BACKGROUND: Ovarian cancer cells in malignant effusions lack attachment to solid-phase matrix substrata and receive survival stimuli through cell-cell and cell-soluble matrix molecule interactions. We hypothesized that adhesion-related survival and proliferation pathway signals can inform clinical outcomes and guide targeted therapeutics. METHODS: Lysed cell pellets from a blinded set of benign (n ¼ 20) and malignant (n ¼ 51) peritoneal and pleural ovarian cancer patient effusions were applied to reverse-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…Consistently, in this study, we found that PXN expression was positively correlated with tumor grade in mRNA profiling of four independent datasets, as well as PXN protein expression difference which was measured by IHC from an independent validation set of samples. The above results indicate both PXN RNA and protein were associated with tumor malignancy, which has been reported in other cancers .…”
Section: Discussionsupporting
confidence: 81%
“…Consistently, in this study, we found that PXN expression was positively correlated with tumor grade in mRNA profiling of four independent datasets, as well as PXN protein expression difference which was measured by IHC from an independent validation set of samples. The above results indicate both PXN RNA and protein were associated with tumor malignancy, which has been reported in other cancers .…”
Section: Discussionsupporting
confidence: 81%
“…In view of the role of the studied proteins in adhesion and intracellular signaling, we investigated their potential association with markers related to these processes that have been previously studied in our effusion material, including proteins analyzed by proteomics (cadherin, FAK, paxillin, pyk, EpCAM, p-ERK, p-AKT) [29], PINCH-2 by flow cytometry [21] and proteins analyzed using IHC, including claudin-1, -3, -4 and -7 [30], the anti-apoptotic proteins XIAP and Survivin [31], p-AKT and p-mTOR [32], and NFkB-p65 [33]. α-parvin was excluded from this analysis in view of its almost universal absence from OC effusions.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of effusion specimens applying proteomics used fresh samples, as well as samples frozen at -20°C or -80°C [89][90][91][92][93].…”
Section: Other Ancillary Testingmentioning
confidence: 99%